Teoria microscópica de ondas de spin em nanofios magnéticos - Sena Filho, Roberto Ferreira (2007)
The dynamical behavior of spins in magnetic materials is affected by its geometry and dimensionality. One can find several new results in the literature exploiting the magnetic properties of low dimension systems with different geometries, since the development of new devices such as: nanosensors, high density magnetic storage, etc., is closely related to new geometries. In this piece of work, we study the propagation of spin waves on cylindrical magnetic nanowires described by a microscopic theory through the Heisenberg Hamiltonian, where we consider the spins fixed at the sites lattice and the transversal section of the wire is hexagonal. Our model takes into account the exchange interaction between the spins that can be ferromagnetic or antifferomagnetic, the interaction of an external field with the spins (Zeeman interaction), anisotropic interactions due to a preferred direction of magnetization, and finally dipole-dipole interactions. The spins are described by boson operators through Holstein-Primakoff representation. The equations of motion for the spins are written in terms of these operators and translational symmetry in a preferential direction allows us to calculate several excitations spectra.